Neosporose equina: Pesquisa de anticorpos no liquido cefalorraquidiano e soro sanguíneo de animais com histórico de ataxia - Stelmann, Ulisses Jorge Pereira [UNESP]; Ullmann, Leila Sabrina [UNESP]; Langoni, Hélio [UNESP]; Amorim, Rogério Martins [UNESP] (My University, 2011)
Equine neosporosis is caused by the protozoans Neospora caninum and N. hughesi. Its clinical signs include hindlimb paralysis, incoordination, ataxia, and abortion. Serum and cerebrospinal fluid (CSF) samples were collected from 38 equines with history of ataxia for indirect fluorescent antibody test (IFAT) in order to detect antibodies to N. caninum. Of the tested serum samples 15/26 (57.6%) were positive, whereas all CFS samples were negative. These seronegative CFS samples suggest that N. caninum has no relation to the manifestation of the neurological clinical signs of ataxia.
Equine neosporosis: Search for antibodies in cerebrospinal fluid and sera from animals with history of ataxia
Keywords: Cerebrospinal fluid; Equine; Indirect fluorescent antibody test (IFAT); Neospora caninum; Neospora hughesi; Serum